Tableau Prep : Up & Running - Allchin, Carl (O'Reilly Media, Inc., 2020)
For self-service data preparation, Tableau Prep is relatively easy to use-as long as you know how to clean and organize your datasets. Based on the popular blog Preppin' Data, this practical guide takes you step-by-step through the fundamentals of data preparation using this popular tool. Carl Allchin from the Data School in London provides a series of lessons to get you up to speed on Tableau Prep, including methods for cleaning and organizing your datasets. In just a short time, this tool has filled a valuable niche for self-service data preparation in the same way Tableau Desktop has for self-service data analytics. This book gets you started with Tableau Prep right away. Learn fundamental data preparation strategies for approaching complex challenges Understand how to apply those skills in more depth with Tableau Prep Manage projects that require data preparation with more confidence Learn how Tableau Prep will empower you to make informed decisions.